Smart suits, tattered boots: black ministers mobilizing the Black church in the twenty-first century - Edwards, Korie L. (New York University Press, 2022)
"A compelling study of how race, culture, and civic organizing impact black religious leader mobilization in contemporary America. Black ministers were at the heart of the Civil Rights movement, but in recent years their level of social mobilization has decreased, with much of their efforts being devoted to supporting the candidacies of Democratic politicians. This book explores the question of when and why black ministers mobilize for change, and attempts to explain their relative lack of involvement in the Black Lives Matter movement and the broader movement for police reform"--